Integrated analysis of proteomics and metabolomics in infantile epileptic spasms syndrome - Jun Chen; Xiaoqian Wang; Xueyi Rao; Huan Luo; Yajun Shen; Jing Gan (Scientific Reports)
Abstract Infantile Epileptic Spasms Syndrome (IESS) is a severe developmental epileptic encephalopathy that manifests in infancy, significantly impacting the health and quality of life of affected children. The treatment of IESS poses a significant challenge, primarily due to the incomplete understanding of its etiology and pathogenesis. Objective: This study aims to investigate the pathogenic mechanisms of IESS, utilizing metabolomics and proteomics analyses to uncover potential biomarkers for the disease, thereby providing new insights for diagnostic and therapeutic strategies. Cerebrospinal fluid samples from 6 IESS patients and 6 control subjects with benign intracranial hypertension were collected and analyzed using metabolomics and proteomics techniques. Significant differential metabolites and proteins were identified and correlated to determine key proteins associated with specific metabolites. The study then expanded the sample size to 10 per group and validated the identified proteins through ELISA analysis. A total of 24 differential metabolites (12 upregulated and 12 downregulated) and 79 differential proteins (18 upregulated and 61 downregulated) were identified. Metabolomic analysis suggests that linoleic acid is a highly noteworthy differential metabolite in the cerebrospinal fluid of IESS patients. The associated differential protein HLA-A and SEZ6L2 proteins were notably downregulated (p < 0.05). Linoleic acid and its metabolism-related proteins HLA-A and SEZ6L2 could serve as potential biomarkers for IESS, providing new insights into the complex pathogenic mechanisms of the disease. Additionally, these findings also assist in identifying new therapeutic targets and developing more effective treatment strategies.